Emisi Metan Sektor Pertanian Kampung Iklim Desa Mukti Jaya Kecamatan Rimba Melintang Kabupaten Rokan Hilir Provinsi Riau - Yenny Desvita; Erwin Erwin; Yanuar Yanuar; Zulfan Saam (Universitas Riau, 2019)
Methane emissions of agriculture sector in Indonesia from year to year increase. To reduce the rate of methane emissions increase, the Indonesian government in 2012 through the Ministry of Environment launched the Kampung Iklim program. One of the villages included in Kampung Iklim Program is Mukti Jaya Village, Rimba Melintang Sub-district, Rokan Hilir Regency, Riau Province. This research aims to analyze methane emission model of agriculture. The research was conducted through survey by field research method. Research location in Mukti Village Rimba Melintang District Rokan Hilir Regency Riau Province. The value of methane rice land emissions in Mukti Jaya Village from 2011-2015 has increased due to changes in some methane producing parameters. The use of Cisadane varieties produced the highest methane emissions compared to the Ciherang and Dodokan varieties of 0.00029 Gg CH4/year/ ha.